Teaching Translation through STAD (Students Team Achievement Division) Technique - Rahmawati Upa; Muhammad Resqi Ridho (Jurnal Studi Guru dan Pembelajaran, 2019)
This research aims at finding out whether or not the use of STAD technique in teaching translation is effective to improve students’ translation ability at English Education Program, Faculty of Teacher Training and Education. The population in this research was fifth semester students in academic year 2019. The researchers use pre-experimental method with pre-test and post-test design, and translation test as instrument of this research. Then the researchers analysed the data by using Statistical Product and Service Solution (SPSS) program. The researchers conclude that using Students Team Achievement Division (STAD) technique to teach translation in the fifth semester students of English Education Program is effective. It is proven by mean score of the students in the post-test (80.20 (good)) is higher than mean score of students in the pre-test (68.87 (fairly good)). The researchers also found that the p value (0.00) on t-test is lower than α (0.05). It indicates that the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It can be concluded that teaching by using STAD technique is effective in improving students’ ability in translation.